Perceived descriptive norms for alcohol use among tribal college students: Relation to self-reported alcohol use, consequences, and risk for alcohol use disorder. (March 2020) - Larimer, Mary E.; Parker, Myra; Lostutter, Ty; Rhew, Isaac; Eakins, Danielle; Lynch, Alex; Walter, Theresa; Egashira, Leo; Kipp, Billie Jo; Duran, Bonnie
Abstract: This research addressed gaps in the literature by testing relationships between perceived descriptive alcohol use norms and individual's own alcohol use and consequences among tribal college and university (TCU) students. Survey data were collected from 3239 tribal college students in 22 TCUs across the United States in 2015 and 2016, of whom 3174 provided usable data on the variables of interest for the current manuscript. Results indicated students misperceived the descriptive norms for alcohol use at their TCU, on average estimating students at their college drank more frequently, more per occasion, and more total drinks per week relative to the observed averages on these outcomes. Participants' own drinking was significantly related to their perceived norms, with higher perceived norms related to more drinking. In addition, higher perceived norms were associated with greater alcohol-related negative consequences and lower likelihood of being a non-drinker. These findings extend research with students at majority-serving colleges and universities, indicating normative misperceptions exist and have similar relationships to alcohol use and consequences among TCU students nationwide. These findings support adaptation of normative feedback interventions for use with TCU students to emphasize healthy alcohol norms and correct misperceptions that support the stereotype that all students drink to excess.